Attitudes toward individuals with opioid use disorders and criminal justice involvement: An experimental vignette study - DePue, M. Kristina (Journal of addictions & offender counseling, 2024)
Providing moderate levels of treatment to individuals with a criminal justice history is associated with lowered rates of recidivism; yet, treatment access remains low. One possible factor contributing to the lack of treatment options is public stigma. An experimental study was conducted that tested for differences in stigmatizing attitudes across conditions: (a) major depressive disorder (MDD), (b) MDD and opioid use disorder (OUD), and (c) MDD, OUD, and nonviolent, drug-related criminal histories. Findings indicate that individuals who meet the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, criteria for OUD with MDD, regardless of criminal histories, are stigmatized at higher levels than those with MDD alone.